Time Synchronization Algorithms Based on Timing-Sync Protocol in Wireless Sensor Networks - Kulaklı, Ali Burak; Erciyeş, Kayhan; Erciyeş, Kayhan (Institute of Electrical and Electronics Engineers Inc., 2008)
Wireless Sensor Networks(WSN) are large scale networks of sensors running on wireless environment. For an application running on a WSN, gathered data by the sensors are time critical in most of the cases. However, almost all the nodes suffer from a problem named clock drift. This problem causes clock difference among nodes as time goes because the processors do not run exactly at the same speed. There are many proposed solutions to remedy this problem. TPSN (Timing-sync Protocol for Sensor Networks) is one of the effective protocols proposed to synchronize sensor networks. In this paper, we propose enhancements over TPSN to synchronize nodes in a wireless sensor network more effectively with a lower message complexity and higher precision.
23rd International Symposium on Computer and Information Sciences, ISCIS 2008; Istanbul; Turkey; 27 October 2008 through 29 October 2008
Keywords: Wireless sensor networks; Clustering algorithms; Time synchronization; Timing-sync Protocol for Sensor Networks